Jami and Medieval Philosophy in the Studies of Y.E. Bertels - Nasridinovich, G’ovsidinov Maruf (European Journal of Life Safety and Stability (2660-9630), 2021)
The article analyzes the scientific heritage of the orientalist Y. E. Bertels and reveals the role and significance of the spiritual heritage of Abdurahman Jami in medieval philosophical science.The peculiarities of Jami’s philosophical views and his contribution to the development prospects of science are discussed in detail.